2013
DOI: 10.2478/raon-2013-0056
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human erythropoietin alters gene expression and stimulates proliferation of MCF-7 breast cancer cells

Abstract: BackgroundFunctional erythropoietin (EPO) signaling is not specific only to erythroid lineages and has been confirmed in several solid tumors, including breast. Three different isoforms of erythropoietin receptor (EPOR) have been reported, the soluble (EPOR-S) and truncated (EPOR-T) forms acting antagonistically to the functional EPOR. In this study, we investigated the effect of human recombinant erythropoietin (rHuEPO) on cell proliferation, early gene response and the expression of EPOR isoforms in the MCF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…EPO can stimulate the growth of EPO-R-positive tumor cells and thereby enhance patient tumorigenesis (30,31). In response to chimeric activator exposure, we compared proliferation of EPO-R-positive MCF-7 and BT-549 cells with EPO-R-negative HeLa cells (30,31). MCF-7 and BT-549 cell lines responded to 10F7-EPO (logEC 50 = −6.7 M) but not 10F7-EPO R150A ; HeLa cells did not significantly respond to either protein.…”
Section: Resultsmentioning
confidence: 99%
“…EPO can stimulate the growth of EPO-R-positive tumor cells and thereby enhance patient tumorigenesis (30,31). In response to chimeric activator exposure, we compared proliferation of EPO-R-positive MCF-7 and BT-549 cells with EPO-R-negative HeLa cells (30,31). MCF-7 and BT-549 cell lines responded to 10F7-EPO (logEC 50 = −6.7 M) but not 10F7-EPO R150A ; HeLa cells did not significantly respond to either protein.…”
Section: Resultsmentioning
confidence: 99%
“…Concern has been identified that erythropoiesis-simulating agents are associated with decreased tumor progression and survival. (4446) In this context, some centers are exploring the effects of agents such as romiplostim (a thrombopoietin receptor agonist) to maintain platelets >100 × 10 9 /L in patients being treated with cytotoxic chemotherapy. Limited data report a 15% DVT rate and are not adequate to consider impact on progression and/or survival.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years functional autocrine/paracrine EPO/EPO-R systems have been described in human cancer cells originating from breast cancer, cervical cancer, melanoma and prostate cancer. These data suggest that the EPO/EPO-R axis may affect tumor growth, progression and metastasis [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 81%